PENGARUH BORAKS TERHADAP KUANTITAS SPERMA MENCIT (Mus musculus) - Rosa, Yunilda (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2013)
The use of food additive such as borax has a negative effects on health, example the abuse of borax as food additive in the pempek and bakso can be dangerous for human health at Palembang city. The borax or boric acid have toxic effect on all body cells.  The purpose of the  research is to assess the effect of borax on the quantity of mice sperm, how many are the borax doses can cause decrease the quantity of sperm mice. The research  was carried out at laboratory Department of Medical biology, Faculty of Medicine Sriwijaya University Palembang using a Completely Randomized Design. The treatment group give the borax, the control group was administrated by similar volume of aquabidest only. The result showed that borax could significantly  decreased (P<0,05) the number of mice  sperm concentration compared to control  group. As  a conclusion the administration of borax at doses 4 mg/10 gr bw and 6 mg/10 gr bw on male mice by gavage in 35 days can significantly decrease the quantity of mice sperm compared to the control  group. It is suggested  to conduct further studies such as the fertility test  of mice sperm given  borax longer than 35 days by  gavage. Key words:   Borax, The quantity of sperm and Mus musculus